MUDHARABAH PRINCIPLE OF BANKING PRODUCTS - Khudari Ibrahim (Jurnal IUS Kajian Hukum dan Keadilan, 2014)
Mudharabah principle is the uniquely part of Islamic banking products, because it has a philosophical difference between the conventional banking system and Islamic banking that followed the principle split profit or losses. Mudharabah is a venture capitalists partnership include owner (sahib al - mal) and entrepreneurs (mudharib), aiming to make a profit (al-ribh) and divided as agreement in the contract. The scheme is divided into types mudharabah muthlaqah (unrestricted investments) and Mudharabah muqayyadah (investment tied). Application of the provisions of mudharabah governed according to Islamic principles as mandated by the laws of Islamic banking. Mudharabah arrangement according to the perspective of law codified in the form of classical literature form the Islamic principles of ijtihad of the scholars in context of traditional patterned times. While in modern, mudharabah arrangement has grown to be a part of Islamic banking products based on The Sharia National Fatwa Council. According to the positive law perspective, adjustment of the mudharabah principle are listed on Islamic Banking laws that clarified by the Regulation of Bank Indonesia as the rule of procedure. Application of the principle of mudharabah in the agreement (contract) in Islamic banking contained the improvisation about insurance which unregulated through the National Fatwa Council and because it is violate Sharia principles of Sharia compliance.Keyword : mudharabah principle, partnership and Islamic Banking.